Une internationalisation disputée - Antoine Roger (Revue d’Histoire des Sciences Humaines)
The way rural sociology has developed in Romania cannot be reduced to a simple confrontation between those advocating research aligned with international standards and those defending a grass-roots science, attuned to local realities. The positions and stances of the protagonists have gradually shaped a scientific field. Some of those who had participated in international academic forums under the Communist regime used this to further their position in the new context; others had to handle the new capitalism of the post-Soviet era, and likewise laid claim to international academic recognition. In both cases, combinations with complementary social profiles created tension between the sociologists who wished to integrate studies on rural populations into broader analyses, and those who believed in the production of specialised knowledge. So this particular organisation of the field has a long history. The antagonisms it sustains and the comparisons it authorises lend themselves to structural comparison.